Application analysis of WCDMA wireless communication system in coal mine - ZHANG Xiao-guang; LI Jun (Gong-kuang zidonghua, 2013)
In view of requirements to wireless communication system of coal mine at present, the paper analyzed and compared characteristics of existing mine-used wireless communication systems, described advantages of WCDMA mine-used wireless communication system, and analyzed its key technologies, introduced network architecture and function characteristics of the system too. The application result shows that the system can meet communication needs of daily production management of coal mine.